A review on urban air quality, global climate change and CDM issues in the transportation sector. (15th July 2009) - Labriet, Maryse; Caldes, Natalia; Izquierdo, Lucila
Although their potential for reducing both Greenhouse Gases (GHGs) and local air pollutants is considered significant, transportation projects remain an almost negligible part of the Clean Development Mechanism (CDM). Inspired by the CURB-AIR project, this paper reviews several case studies focused on Bus Rapid Transit (BRT) and biofuels in the context of CDM. The key difficulties associated with BRT and biofuel CDM projects are, among others, the complex development of the CDM baseline and monitoring of the CDM methodologies; the difficulty to obtain the significant requested investments (especially for BRT); the need to ensure a good quality and reliable supply chain of biofuels; and the relatively small expected 'carbon revenues' compared to the total cost. It appears that a better quantification and accountability of all the sustainability aspects and co-benefits beyond air pollution reduction would be required in order to promote CDM and, more generally, sustainable transport projects in developing and emerging countries.